Analysis of Antecedents and Impact of Work Involvement of Non-ASN Employees in The Government Environment of The Riau Islands Province - Mahira, Rafika; Hefri Ariyanto, Hepy (Dinasti International Journal of Education Management and Social Science, 2025)
To achieve competitive advantage, organizations must continue to follow technological developments and implement them effectively. In addition, it is important for organizations to focus on Transformational Leadership, Job Satisfaction , and Organizational Culture through Work Engagement so as to create a productive and innovative work environment. With this approach, organizations will not only improve performance but also create a positive work culture for all parties. This study aims to analyze the influence of antecedents and consequences of Employee Performance of Non-ASN Employees in the Riau Islands Provincial Government Environment with Work Engagement as a mediating variable. The research sample is Non-ASN employees in the Riau Islands Provincial Government Environment. By using convenience sampling techniques, 340 responses were obtained from Non-ASN employees through questionnaires distributed online using Google Form. The research model analysis method uses Partial Least Square (PLS) with SMART PLS Ver 3.0 software. Empirical findings prove that Transformational leadership has a positive effect on employee performance . While Job satisfaction and organizational culture do not directly affect employee performance , but the mediating effect through work engagement can have a significant effect on employee performance. The results of this study have managerial implications in increasing work engagement, employees must feel satisfied and supported by a strong organizational culture to be more active and innovative, and facilitate the achievement of desired results.